Preparation of a solid dispersion of Euptox A and evaluation of its biological activity and safety - Haojun Li; Runa Zhao; Wei Zhou; Zhili Li; Wenlong Chen (PLoS ONE, 2025)
Terrestrial mollusks are common agricultural pests that often infest crops for a long time during the growth stage and create holes or notches in vegetable leaves, especially seedlings and young leaves. In this study, a solid dispersion (SD) of Euptox A and polyethylene glycol-4000 was prepared via the melting method. The drug-to-carrier ratio, melting temperature, and cooling temperature of Euptox A SD were optimized. Euptox A SD was tested against Bradybaena ravida, Limax maximus, and Oncomelania hupensis for 48 and 72 h. The toxicity of Euptox A SD was equivalent to that of 10%Meta, a traditional chemical softener. Moreover, the rate of apoptosis in human liver cells (L02) caused by Euptox A SD was low. The toxicity of Euptox A SD to Pheretima tschiliensis was low, and the normal development of Brassica campestris was not affected. These results indicate that Euptox A SD can be used as an alternative molluscicidal.